The case for neuregulin-1 as a clinical treatment for stroke - Noll, Jessica M.; Sherafat, Arya A.; Ford, Gregory D.; Ford, Byron D. (Frontiers in Cellular Neuroscience, 2024)
Ischemic stroke is the leading cause of serious long-term disability and the 5 th leading cause of death in the United States. Revascularization of the occluded cerebral artery, either by thrombolysis or endovascular thrombectomy, is the only effective, clinically-approved stroke therapy. Several potentially neuroprotective agents, including glutamate antagonists, antiinflammatory compounds and free radical scavenging agents were shown to be effective neuroprotectants in preclinical animal models of brain ischemia. However, these compounds did not demonstrate efficacy in clinical trials with human patients following stroke. Proposed reasons for the translational failure include an insufficient understanding on the cellular and molecular pathophysiology of ischemic stroke, lack of alignment between preclinical and clinical studies and inappropriate design of clinical trials based on the preclinical findings. Therefore, novel neuroprotective treatments must be developed based on a clearer understanding of the complex spatiotemporal mechanisms of ischemic stroke and with proper clinical trial design based on the preclinical findings from specific animal models of stroke. We and others have demonstrated the clinical potential for neuregulin-1 (NRG-1) in preclinical stroke studies. NRG-1 significantly reduced ischemia-induced neuronal death, neuroinflammation and oxidative stress in rodent stroke models with a therapeutic window of >13 hours. Clinically, NRG-1 was shown to be safe in human patients and improved cardiac function in multisite phase II studies for heart failure. This review summarizes previous stroke clinical candidates and provides evidence that NRG-1 represents a novel, safe, neuroprotective strategy that has potential therapeutic value in treating individuals after acute ischemic stroke.